Iniluence of water deficit on flowering and technological quality sugarcane. - Carlucci, Marisa Vazquez; Ramos, Maria Tereza Baraldi (Pesquisa Agropecuaria Brasileira, 2014)
One test was conducted at the Experimental Station of the Instituto Agronômico, in Campinas, SP, Brazil, in order to study the influence of water stress on flowering and technological quality of sugarcane (Saccharum spp) cultivar IAC 52-150, under greenhouse conditions. The water stress was imposed by interrupting the irrigation until severe moisture stress symptoms in leaf +1 appeared. Subsequently, the irrigation was resuplied until the experiment was terminated. The treatments consisted of water stresses initiated in three different times, as follows: 1) on March 31st, during the floral initiation stage; 2) on April 24th, during the floral formation stage; and 3) on May 24th, at the floral emergence stage. The check plot was continuously irrigated. The evaluation was done on June 24th at the floral maturation stage. At that moment the following parameters were evaluated: a) inflorescence length; b) number of intemodes, length and weight of stalks; and c) technological quality. The inflorescence development was mainly affected when irrigation stopped during the floral formation stage. The interruption of irrigation during floral emergence stage also affected the inflorescence length. The treatments did not affect the number of Internodes but reduced the final length and weight of stalks, mainly when the Irrigation was stopped during the floral initiation stage. Treated plots showed a decrease in pol, brix and juice purity as well as in estimated recoverable sugar content. On the other hand, the reducing sugar contents increased in the treatments B and C. Fiber content and juice volume didn't show significant variation among variation under water stress.